Webometrics ranking of Universities: fallacy or reality (African Journal of Science, Technology and Social Sciences, 2024)
In recent years, the utilization of webometrics as a tool for ranking universities has gained significant traction, purportedly offering a comprehensive assessment of institutions' digital presence and impact. However, amidst its growing popularity, questions arise regarding the validity and applicability of webometrics rankings, particularly concerning universities situated in the global south. This paper critically examines the webometrics ranking system, aiming to discern its strengths and weaknesses while scrutinizing its efficacy in evaluating universities, particularly those in regions with diverse socio-economic contexts and digital infrastructures. The analysis begins by delineating the fundamental principles underlying webometrics rankings, highlighting its reliance on web-based indicators such as web presence, visibility, and transparency. While these metrics ostensibly offer insights into universities' global reach and influence, they also engender methodological complexities and biases. Notably, the dominance of older well-endowed institutions in comparison with younger resource-constrained institutions impeding equitable evaluation. Furthermore, the paper investigates the specific challenges faced by universities in the global south within the webometrics framework. Issues of digital divide, limited internet penetration, and disparities in web accessibility compound the difficulties faced by these institutions in attaining favorable rankings. Moreover, the emphasis on quantitative metrics overlooks qualitative aspects of academic excellence, neglecting factors such as research impact, teaching quality, and societal relevance, which are integral to universities' roles in diverse contexts.Through a critical lens, this paper underscores the fallacies inherent in the uncritical adoption of webometrics rankings as a singular measure of university performance. It advocates for a nuanced approach that acknowledges the contextual nuances and challenges faced by universities, particularly in the global south. By fostering a dialogue on the limitations of webometrics and exploring alternative evaluation methodologies, this research aims to contribute to a more inclusive and equitable framework for assessing higher education institutions in an increasingly digitized world.
Keywords: Web rankings; University ranking; Webometrics; Scientometrics